Variability of the kinetic energy in seasonally ice-covered oceans. - Martínez-moreno, Josué; Lique, Camille; Talandier, Claude; Jamet, Quentin; Treguier, Anne-marie (Authorea, Inc., 2024)
The seasonality of Arctic sea ice cover significantly influences heat, salt, buoyancy fluxes, ocean-ice stresses, and the potential and kinetic energy stored in the ocean mixed layer. This study examines the seasonal variability of oceanic scales and cross-scale flux of kinetic energy in the seasonally ice-covered Arctic, using a high-resolution, idealized coupled ocean-sea ice model. Our simulations demonstrate pronounced seasonality in the scales of oceanic motion within the mixed layer, governed by distinct mechanisms during summer and winter. In summer, an inverse energy cascade sustains mesoscale dynamics and enhances kinetic energy. In winter, ice-induced dissipation suppresses kinetic energy and mesoscale, allowing only the persistence of submesoscale processes. These results underscore the critical role of sea ice in modulating the seasonal dynamics of oceanic motion and their dominant scales, a behavior markedly different from that in the open ocean. Thus, understanding these coupled processes is essential for improving predictions of the ocean's energy evolution as the Arctic transitions toward a summer ice-free regime.